CONSTITUENT ELEMENTS OF CARE: (DIS)CONNECTIONS THAT CHALLENGE THE INTEGRALITY IN HEALTH FOR INDIGENOUS PEOPLE WITH TUBERCULOSIS - Jesus, Saionara Santana de; Freitas, Maria Yaná Guimarães Silva; Servo, Maria Lúcia Silva; Santana, Neuranides; Rodrigues, Ivana Silva; Santos, Guilherme de Brito; Silva, Shâmia Sousa (Cogitare Enfermagem, 2024)
Objective: To analyze the production of care, regarding reception, bonding, resolvability, and accountability, for indigenous people with tuberculosis. Method: Qualitative study, with systematic observation, document analysis, and semi-structured interviews with health workers and indigenous health management and the municipal health department of Banzaê/Bahia - Brazil. Data triangulation was carried out from interviews, documentary records, and field observation. Results: The reception is given when the need for understanding and respect for cultural specificities is recognized, the bond is related to the health worker's culture, the resolvability is hindered due to municipal management, and there are divergences among those responsible for indigenous health in taking responsibility for care. Conclusion: Collective actions are necessary between the municipal, state instances and the Special Indigenous Sanitary Districts, regarding the path of the health services network.